Strategi Peningkatan Penjualan Produk Melalui Pendekatan Unique Selling Point Dalam Menunjang Eksistensi Bisnis HNI HPAI - Anggit Dyah Kusumastuti (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2022)
Unique Selling Point (USP) is the uniqueness of a business (product), this uniqueness is different with the other types of business and product. This research aims to determine the marketing strategy of unique selling point (USP) carried out by HNI products in creasing their sales so that consumers do not switch to the product competitor company’s. This type of research uses descriptive analysis. The result show that the unique selling point of HNI product through promotion activities using book catalog, brochures, x-banner, website HNI, and whatsapp group in promoting and describing the content of each product that has been certified halal and product price in accordance with market condition.